Coronary CT angiography : radiation dose measurements and image quality assessments - Sabarudin, Akmal (Curtin University, 2012)
Prospective ECG-triggering is regarded as one of the most effective approaches for reduction of radiation dose to patients during coronary CT angiography (CCTA). This study was conducted to investigate the diagnostic performance of prospective ECG-triggered CCTA with regard to the image quality and dose reduction, based on a multi-centre research. The research was performed in four stages, with stage 1 investigating the different CT scanning protocols and conventional angiography procedures with corresponding radiation dose measurements; stage 2 focused on the analysis of radiation dose in patients undergoing different generations of multislice CT scanners; stage 3 conducted a survey among medical specialists and radiographers with the aim of obtaining opinions regarding the benefits and difficulties in performing prospective ECG-triggered CCTA; stage 4 analysed image quality and radiation dose in patients undergoing single-source and dual-source 64-slice CT coronary angiography with use of prospective ECG-triggering.Stage 1 is a pilot study conducted on an anthropomorphic phantom. In this experiment, the radiation dose was compared between the invasive coronary angiography (ICA) and CCTA. These imaging protocols for ICA included the standard angular projection views with different magnifications. These ICA protocols were compared with several CT protocols including prospective and retrospective ECG gating. In addition, tube current modulation was applied in retrospective gating protocol. The radiation dose was also measured at the selected radiosensitive organs including breast and thyroid gland. Although ICA produced lower radiation dose than CCTA, application of modified techniques in both CCTA and ICA is recommended in clinical practice for further radiation dose reduction.Stage 2 involved a retrospective analysis of radiation dose in patients undergoing prospective ECG-triggered CCTA with different CT generations including single-source 64-slice CT (SSCT), dual-source 64-slice CT (DSCT), dual-source 128-slice CT and 320-slice CT based on several hospitals in Perth, Western Australia and Kuala Lumpur, Malaysia. A total of 164 patients undergoing prospective ECG-triggered CCTA with different types of CT scanners were studied. The analysis showed that the mean effective dose was estimated at 6.8 mSv, 4.2 mSv, 4.1 mSv, and 3.8 mSv, corresponding to 128-slice DSCT, 64-slice DSCT, 64-slice SSCT and 320-slice CT scanners, respectively. A positive relationship was found between effective dose and body mass index (BMI) in this study. Low radiation dose was achieved in prospective ECG-triggered CCTA, regardless of any CT scanner generation. BMI is identified as the major factor that has a direct impact on the effective dose associated with prospective ECG-triggered CCTA.A well-designed survey was performed in stage 3 among specialists and radiographers from 6 national health institutions in Malaysia in order to explore the opinion concerning the benefits and difficulties in performing prospective ECG triggered CCTA. In total, 53 responses were received (85%), comprising specialists (21%) and radiographers (79%). Across all the respondents, the main benefits of prospective triggering were agreed as: radiation dose reduction, image quality improvement and patients’ output increases. On the other hand, the issue of heart rate was agreed by all respondents as a main challenge when performing prospective triggered CCTA. The remaining challenges such as difficulty in obtaining cardiac functional assessments, diagnostic accuracy concerns and data processing management issue have been seen to vary according to the groups of respondents and the scanner type. Radiation dose reduction seems to be the main benefit, which is most agreed upon, while the issue of the heart rate is seen as the main challenge in prospective ECG-triggered CCTA.Finally, stage 4 is a comparative study consisting of quantitative and qualitative analysis, and it was conducted to investigate the image quality and radiation dose performance between retrospective gated and prospective ECG triggered CCTA with use of 64-slice SSCT and DSCT. The SSCT component was performed in the Royal Perth Hospital, Western Australia, while the DSCT component was conducted in the National heart Institute, Kuala Lumpur, Malaysia. A total of 209 patients who underwent CCTA with suspected coronary artery disease (CAD) scanned with SSCT (n=95) and DSCT (n=114) scanners using prospective ECG-triggering and retrospective ECG-gating protocols. The image was qualitatively assessed by two experienced observers, while quantitative assessment was performed by measuring the image noise, the signal-to-noise ratio (SNR) and the contrast-to-noise ratio (CNR).A total of 2,087 coronary artery segments were evaluated. Both DSCT and SSCT resulted in good image quality, regardless of prospective or retrospective gating protocols. Although radiation dose calculated between DSCT (6.5 mSv) and SSCT (6.2 mSv) showed no significant difference, the effective dose in prospective triggering was significantly lower than that in retrospective gating protocol. The results indicated that in the retrospective gating protocol, the effective dose with DSCT (18.2 mSv) was also significantly lower than that in SSCT (28.3 mSv). This study confirmed that prospective ECG triggered CCTA reduces radiation dose significantly compared to retrospective ECG-gating CCTA, while maintaining good image quality.In summary, the results of this project show that coronary CT angiography with prospective ECG-triggering is a reliable diagnostic technique with resultant very low radiation dose, but still maintaining diagnostic images. With widespread use of coronary CT angiography in the diagnosis of coronary artery disease, increased awareness of radiation dose associated with coronary CT angiography is of paramount importance, and application of dose-reduction strategies is highly recommended for routine clinical practice.